2022
DOI: 10.1538/expanim.22-0008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lysosomal-associated protein transmembrane 5 ameliorates cardiac function and inflammatory response by inhibiting the nuclear factor-kappa B (NF-κB) pathway after myocardial infarction in mice

Abstract: Myocardial infarction (MI) as the remarkable presentation of coronary artery disease is still a reason for morbidity and mortality in worldwide.Lysosomal-associated protein transmembrane 5 (LAPTM5) is a lysosomal-related protein found in hematopoietic tissues and has been confirmed as a positive regulator of pro-inflammatory pathways in macrophages. However, the role of LAPTM5 in MI remains unknown. In this study, we found that both mRNA and protein expression levels of LAPTM5 were significantly elevated in MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…LAPTM5, a multifunctional protein, has been implicated in several cellular processes, including autophagy [ 50 ], lysosomal stabilization [ 51 ], apoptosis [ 52 ], and inflammation [ 23 , 53 ]. Its role as a pro-inflammatory factor has been well-established in macrophages [ 53 ] and myocardial infarction [ 23 ]. In this study, we found that LAPTM5 positively correlated with IL-1β、IL-6, TNF-α, and IL-8 in TECs of DKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAPTM5, a multifunctional protein, has been implicated in several cellular processes, including autophagy [ 50 ], lysosomal stabilization [ 51 ], apoptosis [ 52 ], and inflammation [ 23 , 53 ]. Its role as a pro-inflammatory factor has been well-established in macrophages [ 53 ] and myocardial infarction [ 23 ]. In this study, we found that LAPTM5 positively correlated with IL-1β、IL-6, TNF-α, and IL-8 in TECs of DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its established roles in these contexts, the function of LAPTM5 within the framework of DKD remains largely unexplored [ 22 ]. Previous studies showed that LAPTM5 may play a role in mitigating inflammation [ 23 , 24 ], and a key factor in the pathogenesis of DKD. This finding suggests that LAPTM5 could potentially represent a novel therapeutic target or biomarker for DKD.…”
Section: Introductionmentioning
confidence: 99%
“…Among the Fc receptors, Fcgr2b could serve as one marker of the pro-inflammatory phenotype of microglia after TBI [77][78][79]. There was some evidence that Laptm5 had pro-inflammatory properties in macrophages [80]. In a chronic constriction injury in rats, Laptm5 was identified as a significant upregulated neuroinflammation-related gene that influenced neuropathic pain behavior [81].…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin might play a role in regulating MI inflammation through its interaction with NF-κB. Both the Wnt/β-catenin pathway and NF-κB were activated after MI ( Song et al, 2022 ). NF-κB is a major transcription factor in the inflammatory response that can promote the expression of proinflammatory factors and enzymes.…”
Section: β-Catenin and Cardiac Diseasesmentioning
confidence: 99%